Is there life after policy streams, advocacy coalitions, and punctuations: using evolutionary theory to explain policy change? - John, Peter (2003)
This article reviews the current state of public policy theory to find out if researchers are ready to readdress the research agenda set by the classic works of Baumgartner and Jones (1993), Kingdon (1984) and Sabatier and Jenkings-Smith (1993). After reviewing the influences of institutional, rational choices, network, socio-economic and ideational approaches, the article pays tribute to the policy streams, punctuated equilibrium and policy advocacy coalition frameworks whilst also suggesting that future theory and research could identify more precisely the causal mechanisms driving policy change. The article argues that evolutionary theory may usefully uncover the micro-level processes at work, particularly as some the three frameworks refer to dynamic models and methods. After reviewing some evolutionary game theory and the study of memes, the article suggests that the benefits of evolutionary theory in extending policy theories need to be balanced by its limitations. - Reproduced.
Keywords: Public policy